Neighbors : a novel - Steel, Danielle (New York : Random House Large Print Publishing, 2021)
"Meredith White was one of Hollywood$1 (Bs most recognizable faces. But a personal tragedy cut her acting career short and alienated her from her family. For the last fifteen years, Meredith has been living alone in San Francisco with two trusted caretakers. Then, on a muggy late summer day, a massive earthquake strikes Northern California, plunging the Bay Area into chaos. Without a moment$1 (Bs hesitation, Meredith invites her stunned and shaken neighbors into her mostly undamaged home as the recovery begins. These people did not even realize that movie star Meredith White was living on their street. Now, they are sharing her mansion, as well as their most closely kept secrets. Without the walls and privacy of their own homes, one by one, new relationships are forged. For every neighbor there is a story, from the doctor whose wife and children fear him, to the beautiful young woman dating a dishonorable man, to the aspiring writer caring for a famous blind musician. In the heart of the crisis, Meredith finds herself venturing back into the world. And thanks to the suspicions and the dogged detective work of a disaster relief volunteer, a former military officer named Charles, a shocking truth about her own world is exposed. Suddenly Meredith sees her isolation, her estranged family, and even her acting career in a whole new light."--s
Keywords: Motion picure actors and actresses -- Fiction; Neighbors -- Fiction; Earthquakes -- California -- Fiction; Large type books